Effect of the FecB gene on greasy fleece yield and milk yield of Garole x Malpura sheep - MISHRA, A K; KUMAR, S; KOLTE, A P; ARORA, A L; SINGH, V K (The Indian Journal of Animal Sciences, 2011)
The present study eas undertaken to evaluate the effect of FeeR gene on first greasy fleece yield (OFY) and average daily milk yield (ADMY) in Garole x Malpura (GM) crossbreds. OM sheep (144) were genotyped by forced PCRRFLP technique, out of that, 14 were homozygous (FeeBBB ). 89 heterozygous (FecBB+) and 41 non-carriers (FecB++) for the FecB gene. The majority (71.5%) of GM individuals carried the FecB gene. The FecB genotype significantly affected the first GFY and it was lower in FecBBB as compared to FecBB+and FecB++ individuals. The generation did not affect the first GFY, however, it was higher in F3 followed by F1 and F2 generation. The FecB genotype significantly affected the ADMY, and it was greater in FecB++ ewes than that in FecBB+ and FecBBB ewes. The ADMY of eVles carrying FecB gene bearing twin lambs was 28.42% higher than that of ewes carrying FecB gene bearing single lamb. Lambing year and generation did not affect the ADMY, while type of birth, parity, and week of lactation significantly affected the ADMY in GM ewes. The results indicated that GM ewes carrying FecB gene bearing twin lambs are capable of producing good amount of milk in semi-arid tropical climate. Â